Using teacher action research to promote constructivist learning environments in mathematics classes in South Africa - Sebela, Mokgoko Petrus (Curtin University, 2003)
The present research examined whether teachers in South Africa could use feedback from a learning environment instrument to help them to increase the degree to which they emphasised constructivist-oriented teaching strategies in their classroom. The study also investigated the validity of a widely-applicable classroom environment questionnaire, as well as associations between attitudes and classroom environment. The study involved a combination of quantitative and qualitative research methods and was carried out in two phases. In the first phase of the study, data were collected using the Constructivist Learning Environment Survey (CLES), to assess learners' perceptions of the constructivist learning environment, and an attitude scale to assess learners' attitudes towards their mathematics classroom. The instruments were administered to 1864 learners in 34 intermediate (Grades 4 - 6) phase and senior phase (Grades 7 - 9) classes. Data were analysed to determine whether (a) the CLES is valid and reliable for use in South Africa and (b) relationships exist between learners' perceptions of the learning environment and their attitude toward their mathematics classes. Descriptive analysis was used to generate feedback information for teachers based on graphical profiles of learners' perceptions of the actual and preferred learning environment for each class. Analyses of data collected from 1864 learners in 34 classes supported the factor structure, internal consistency reliability (Cronbach alpha coefficient), and discriminant validity of the CLES, as well as its ability to differentiate between classes. The results suggest that researchers and teachers can be confident about using the modified version of the CLES in mathematics classes in South Africa in the future.Simple correlation and multiple regression analyses were conducted to examine whether associations exist between learners' attitudes towards their mathematics class and their perceptions of the learning environment. The results indicated that student attitudes were associated with more emphasis on all four CLES scales used. Two scales, Uncertainty and Student Negotiation, were found to contribute most to variance in student attitudes in mathematics classes in South Africa when the other CLES scales were mutually controlled. Descriptive analysis was used to provide information about the constructivist nature of mathematics classes in the Limpopo Province of South Africa. The results indicate that students would prefer a learning environment that is more positive than the one that they perceive as being present in terms of emphasis on all four CLES scales used. The second phase involved a 12-week intervention period during which two teachers used the pretest profiles of actual and preferred classroom environment means to assist them to develop strategies aimed at improving the constructivist orientation of their classroom learning environments. The teachers implemented the strategies and maintained daily journals as a means of reflecting on their teaching practices. Throughout the 12-week period, the researcher made regular support visits that included classroom observations, reviews of daily journals, discussions with teachers and interviews with learners.As well, the researcher had the opportunity of giving support to the teachers in the implementation of their strategies. At the end of the 12 weeks, the CLES was re-administered to learners to determine whether their perceptions of the constructivist emphasis in their classroom learning environments had changed. The posttest graphical profiles indicated that there was a sizeable improvement in teachers' emphasis on CLES dimensions in their classrooms. Apparently, teachers using action research are able to use learners' responses to the CLES to develop and implement strategies for improving their learning environment. The study suggests that journal writing, as a tool used by teachers on a daily basis, can improve their professional expertise as reflective practitioners.